Morning time - Goodhart, Pippa (New York : Franklin Watts, 1997)
Morning time is an enchanting account of a familiar routine at the start of a child's day. While absorbed in the story, your child will be developing important conceptual skills such as an awareness of the passage of time and an understanding of the order of events from beginning to end.
Keywords: Child's routine; Children's stories